2020
DOI: 10.5114/ada.2020.96298
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering subtle nail involvement in lichen planus with dermoscopy: a prospective, controlled study

Abstract: Introduction There are very few studies investigating the dermoscopic aspect of nail involvement in lichen planus and these studies described dermoscopic features of only clinically visible nail involvement in lichen planus. Aim To reveal subtle dermoscopic nail findings in patients with lichen planus. Material and methods The study included 40 patients with lichen planus and 40 healthy volunteers. All fingernails of the patients and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Nail bed dyschromia, nail fold papules, prominent hyponychial vascular structures and lunula variants, such as stippled erythema, homogeneous erythema, flame-shaped lunula, or yellow lunula were not included. [13][14][15][16][17] Studies on Asian and Indian participants showed higher melanonychia frequencies and oral involvement when compared to our study, probably because of the genetic profile of the Brazilian population. [13][14][15][16]18 Characteristics were assessed according to variables without therapeutic response and its importance for an aggressive therapeutic approach.…”
Section: Characteristics Assessed According To Affected Nail Componentmentioning
confidence: 77%
“…Nail bed dyschromia, nail fold papules, prominent hyponychial vascular structures and lunula variants, such as stippled erythema, homogeneous erythema, flame-shaped lunula, or yellow lunula were not included. [13][14][15][16][17] Studies on Asian and Indian participants showed higher melanonychia frequencies and oral involvement when compared to our study, probably because of the genetic profile of the Brazilian population. [13][14][15][16]18 Characteristics were assessed according to variables without therapeutic response and its importance for an aggressive therapeutic approach.…”
Section: Characteristics Assessed According To Affected Nail Componentmentioning
confidence: 77%
“…However, according to some of the publications, there is no consistency in gender predilection. 3,6,[21][22][23][24] The limitations of this study included the low number of cases included in the sample and the performance of a study in a single center and with one operator. Another limitation is the ultrasound threshold that cannot detect abnormalities <0.1 mm at 18 MHz and <0.03 mm at 70 MHz.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a slightly higher number of females in our group is in concordance with some previous clinical studies on the topic. However, according to some of the publications, there is no consistency in gender predilection 3,6,21–24 …”
Section: Discussionmentioning
confidence: 99%
“…The limitation of our report is that the nail involvement of LP was not biopsy-proven. However, we performed dermoscopic examination that is a noninvasive and helpful method to reveal subtle findings in nail involvement of LP [10, 12]. We would like to draw attention to the necessity of thorough clinical and dermoscopic examination of the nails in patients with FFA and/or LPP.…”
Section: Discussionmentioning
confidence: 99%